Impact of Auditor Independence, Professionalism, and Skepticism on Audit Quality - Gunawan, Devina; Ayu Lestari, Mey (Advances in Accounting Innovation, 2025)
Purpose – The objective of this study is to analyze the influence of auditor independence, professionalism, professional skepticism, audit tenure, and auditor competence on audit quality in Indonesia. This study is intended to provide documentation for factors that improve the reliability audits and credibility of financial reporting.Design/methodology/approach –  A quantitative method was used with the primary data in the form of structured questionnaires to auditors of Public Accounting Firms in Surabaya and other cities in Indonesia. Data were tested using structural equation modeling (SEM) to confirm hypotheses and evaluate the relationships found among the variables. Tests of reliability and validity were performed to ensure accuracy of measurement.Findings – This study found that auditor independence, professionalism, professional skepticism, and auditor competence positively and significantly affected audit quality, suggesting that ethical and technical excellence is essential to good audit practices. Conversely, audit tenure has a negative impact on audit quality, which supports the idea that tenure may impair the objectivity of auditors in an extended audit engagement. These results are consistent with regulatory arguments calling for rotation of audit firms and/or partners to bolster professional skepticism and independence.Originality/value – This study fills a gap in the existing literature by providing empirical evidence about the determinants affecting audit quality in the Indonesian setting. The outcomes support policymakers, regulatory agencies, and auditing professionals in reinforcing governance frameworks and audit standards. The study emphasizes the significant role that auditor expertise and ethical behavior plays in upholding the integrity of financial reporting.Research Implications – This study highlights the importance of continuing professional education, and taking action to ensure regulatory compliance, ultimately improving audit quality